2020
DOI: 10.1371/journal.pone.0244538
|View full text |Cite
|
Sign up to set email alerts
|

Social representations and interface layout: A new way of enhancing persuasive technology applied to organ donation

Abstract: Although campaigns promoting organ donation have proved their effectiveness, increasing the number of people who explicitly agree to become donors is still difficult. Based on the social marketing notion of persuasive technology, we reasoned that it was timely to focus on the design of this persuasive technology and to analyze its contribution in particularly challenging contexts such as organ donation. More specifically, the originality of the present study lay in the way we linked the field of persuasive tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 94 publications
0
4
0
1
Order By: Relevance
“…Dependiendo de las razones que los individuos atribuyen al fenómeno de la ansiedad colectiva, y de la durabilidad asociada con ella, las representaciones que este fenómeno son diferentes e implican comunicaciones focalizadas y adaptadas. De hecho, es conocido que las acciones de comunicación son más efectivas cuando se enfocan específicamente en los elementos organizadores de las representaciones sociales (Barbier et al, 2020).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Dependiendo de las razones que los individuos atribuyen al fenómeno de la ansiedad colectiva, y de la durabilidad asociada con ella, las representaciones que este fenómeno son diferentes e implican comunicaciones focalizadas y adaptadas. De hecho, es conocido que las acciones de comunicación son más efectivas cuando se enfocan específicamente en los elementos organizadores de las representaciones sociales (Barbier et al, 2020).…”
Section: Discussionunclassified
“…Depending on the reasons that individuals attribute to a collective anxiety phenomenon and the durability that they associate with it, representations of this phenomenon differ and imply targeted and adapted communications. Indeed, it is known that communication actions are more effective when they specifically target the organizing elements of social representations (Barbier et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Layout design aims to plan the organization of interface information, in order to help users browse content efficiently, reduce users' tasks and cognitive load, and try to solve the problem of disorientation faced by many users [15]. Although the research on interface layout spans many fields, such as online education [17,46,47], e-commerce [48,49] and Man-Machine systems [50,51], its core idea is to optimize the processing process when users receive information, and to improve task performance. A key element in layout design is that the layout needs to meet the information search strategies of different groups.…”
Section: Layout In Interface Designmentioning
confidence: 99%
“…Sulikowski and Zdziebko [48] found that vertical layout is more attractive than horizontal layout in commodity recommendation systems, and the least attractive positions in the interface are at the bottom of the interface (vertical layout) and the right edge of the interface (horizontal layout). Barbier et al [46] stated that users tend to pay more attention to the visual elements in the middle of the interface. They stressed that the key information should be arranged on the interface where the human eye sees it first in the natural state, which can force the user to pay direct attention to the content.…”
Section: Layout In Interface Designmentioning
confidence: 99%
“…Considering the deficient communication from Enedis when deploying the smart technology, shown by the element "Lack of information" in our results, we choose to focus our recommendations on this axis. As previous literature has shown that communication about core elements of social representations rather than peripheral ones is more convincing (Barbier et al, 2020;Zbinden et al, 2011), specific communication on the two key positive aspects of psychological empowerment in the core representations of users, that is, money saving and ecology, may help to increase confidence in the smart device. Communications campaigns jointly executed by private energy suppliers and the public energy distributor could be undertaken.…”
Section: Managerial Implicationsmentioning
confidence: 99%